Rewilding the wildlife in Sangjiangyuan National Park, Qinghai-Tibetan Plateau. Issue 1 (16th December 2020) - Zhao, Xinquan; Xu, Tianwei; Ellis, Jacob; He, Fuquan; Hu, Linyong; Li, Qi
ABSTRACT: The targets of China's national park construction are to protect the authenticity and integrity of the ecosystems, and to achieve the harmonious development between humans and nature. Because of the high intensity of human activities, the authenticity of ecosystems has deviated over the past few decades. It is time to rewild the wildlife and restore the authenticity of these ecosystems. The status of rewilding wildlife in Sanjiangyuan National Park, indicating that the wildlife population, diversity and wildness have increased within the National Park. The wildlife population in the national park has been restored, with about 60, 000 Tibetan antelope, 60, 000 Tibetan gazelle, 36, 000 Tibetan wild ass, 10, 000 wild yak, and 10, 000 white-lipped deer up to 2017. However, overgrazing existed on the alpine grassland with population increasing both of ungulates and livestock.